2020
DOI: 10.1097/ju.0000000000001289
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019: Coronaviruses and Kidney Injury

Abstract: Purpose: The first case of coronavirus disease 2019 (COVID-19) was identified and confirmed in December 2019 in Wuhan, China. COVID-19 is gradually posing a serious threat to global public health. In this review the characteristics and mechanism of kidney injury caused by SARS-CoV, MERS-CoV and SARS-CoV-2 infection are summarized and contrasted. In particular, urine-oral transmission, prevention and management of the kidney injury caused by SARS-CoV-2 are emphasized. Materials and Methods: We searched PubMedÒ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
15
0
1
Order By: Relevance
“…Presence of renal complications in COVID-19 disease is associated with higher rate of diverse outcome including mortality [22]. Previous reports of COVID-19 patients documented that hematuria, proteinuria and AKI are associated with high incidence of ICU admission, acute kidney injury and mortality [17][18][19][20]25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of renal complications in COVID-19 disease is associated with higher rate of diverse outcome including mortality [22]. Previous reports of COVID-19 patients documented that hematuria, proteinuria and AKI are associated with high incidence of ICU admission, acute kidney injury and mortality [17][18][19][20]25].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, AKI has now become an alarming sign and a significant risk factor for mortality in hospitalized COVID-19 patients [7,23,24]. The prevalence of AKI among SARS-CoV-2 infected patients from different countries is variable [25]. Previous studies reported an incidence of AKI among COVID-19 patients ranging from 5 to 29% [8,24,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Our translatome data highlighted early changes in immune response proteins after SARS-CoV-2 infection, which, similar to the global protein profile, succumbed to translational attenuation effects at 48 hpi, particularly in PTC. In contrast, the proteomic profile for the latter continued to increase and could explain the cytokine storm associated with SARS-CoV-2 infection and the pro-inflammatory response-driven changes in kidney pathology ( 53 , 71 , 72 , 73 , 74 ). MERS-CoV infection yielded a similar response although DTC showed a more bidirectional effect.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of highly pathogenic coronaviruses including SARS-CoV, MERS-CoV, and recently SARS-CoV-2 on renal pathology has been largely documented for critically ill patients ( 18 , 53 ). Recent clinical reports suggested a high prevalence of AKI in hospitalized cases of COVID-19 (30–78%) associated with increased mortality rates ( 5 , 6 , 45 , 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…ACE 2 receptors are present on the surface of type1 and type 2 pulmonary epithelial cells, but are also present on other cell types, including endothelial cells in vascular tissues throughout the body (Berger 2020, DiNicolantonio & McCarty 2020, Evans et al 2020, Panfoli 2020. Infection with SARS-CoV-2 in humans is associated with systemic inflammatory reactions, most notably in the lung (Stawicki et al 2020), but also in the digestive tract (Aktas & Aslim 2020, Effenberger et al 2020, Garland et al 2020, Hanrahan et al 2020, Villapol 2020; kidney (Joseph et al 2020, Lv et al 2020; brain (Najjar et al 2020, Vargas et al 2020; liver (Garland et al 2020); skin (Gisondi et al 2020) -most likely via endothelial damage to cutaneous blood vessels (Garduño-Soto & Choreño-Parra 2020) -and heart (Basu-Ray et al 2020, Grimaud et al 2020, Kochi et al 2020, Tahir et al 2020, Zou et al 2020. Reports suggest that SARS-CoV-2-associated vascular endothelialitis may underlie the inflammatory reactions occurring in this spectrum of organ systems (Ackermann et al 2020, Evans et al 2020.…”
Section: Introductionmentioning
confidence: 99%